2011
DOI: 10.31436/iiumej.v12i3.68
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Analysis of Coanda Effect Circulation Control for Wind-Turbine Application Considerations

Abstract: In the efforts to investigate the performance of Coanda Jet in enhancing lift of an airfoil, a numerical study is carried out. Tangential jets that take advantage of Coanda effect to closely follow the contours of the body are considered to be simple and particularly effective in that they can entrain a large mass of surrounding air. This can lead to increased circulation in the case of airfoils, or drag reduction (or drag increase if desired) in the case of bluff bodies such as an aircraft fuselage. Critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…For example, the implementation of CC on an NREL Phase-VI wind turbine led to enhanced circulation with the increment in C µ [76], although the effect was lost at higher wind speeds due to shifting of separation point upstream of the jet. Extensive parametric studies on CC-jets showed the potential of enhancing glide ratio by careful rounding of the trailing edge, along with tailoring of Coanda-jet thickness and momentum coefficient [284,285]. A comparative study on the feasibility of applying CC on a wind turbine presented in [286] reported significant enhancements in lift and drag by separation control and super-circulation.…”
Section: Circulation Controlmentioning
confidence: 99%
“…For example, the implementation of CC on an NREL Phase-VI wind turbine led to enhanced circulation with the increment in C µ [76], although the effect was lost at higher wind speeds due to shifting of separation point upstream of the jet. Extensive parametric studies on CC-jets showed the potential of enhancing glide ratio by careful rounding of the trailing edge, along with tailoring of Coanda-jet thickness and momentum coefficient [284,285]. A comparative study on the feasibility of applying CC on a wind turbine presented in [286] reported significant enhancements in lift and drag by separation control and super-circulation.…”
Section: Circulation Controlmentioning
confidence: 99%
“…3 was explored in Ref. [15]. The design was based upon an annular wing wrapped around a centrifugal flow generator, thus potentially creating a vehicle with no external moving parts and reducing vehicle aerodynamic losses compared to previous V/STOL technologies and substantially eliminating induced drag [15][16].…”
Section: Coandă Mav Progress and Perfectionmentioning
confidence: 99%
“…[15]. The design was based upon an annular wing wrapped around a centrifugal flow generator, thus potentially creating a vehicle with no external moving parts and reducing vehicle aerodynamic losses compared to previous V/STOL technologies and substantially eliminating induced drag [15][16]. Coandă effect offers greater potential at a micro-aerial vehicle scale with regard to fundamental performance parameter "L/D ratio" [17].…”
Section: Coandă Mav Progress and Perfectionmentioning
confidence: 99%
“…To reveal the key elements that could lead to the desired lift enhancement and drag reduction, or a combination of both., without losing generalities and furthering previous studies [31][32][33], the present work critically overviews Coandă jet progress and development and looks into two-dimensional to two-dimensional airfoil in subsonic flow with Coandă jet located at its trailing edge, and devotes special attention to S809 airfoil. For benchmarking, in addition to a clean S809 airfoil, the GTRI Dual Radius CCW airfoil, which has already been investigated thoroughly, is also utilized.…”
Section: Introductionmentioning
confidence: 84%